1984
DOI: 10.1051/jphyscol:1984512
|View full text |Cite
|
Sign up to set email alerts
|

Brillouin Scattering Near Rigid Interfaces

Abstract: R6sum6-Nous donnons un a p e r p des mesures de la diffusion Brillouin prss d'une interface liquide-solide pour differents rapports des impgdances acoustiques des milieux. Nous avons examin6 116thanol, le polycarbonate et les metaux liquides mercure et gallium en contact avec un support de verre solide. Nous prgsentons quelques mesures am6lior6es sur les modes de Lamb et de Love dans les couches minces de polycarbonate sur un support de verre Pyrex. Nous analysons de f a~o n d6taillge une onde du type Stoneley… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

1989
1989
2014
2014

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Experimental studies performed with semiconductor layers supported by metals, have confirmed the importance of adding the elasto-optic contribution to fully interpret the observed spectral features (Sandercock 1978;Loudon and Sandercock 1980). Finally, theoretical studies have been carried out to predict the intensity of surface Brillouin scattering in dielectric and metallic liquids (Dil and Brody 1976;Albuquerque 1983) and the results have been utilized to interpret existing experimental results on alcohols, mercury and gallium (Dil and Brody 1976;Visser et al 1984).…”
Section: Measurements Of Surface Brillouin Scattering On Opaque Matermentioning
confidence: 78%
See 2 more Smart Citations
“…Experimental studies performed with semiconductor layers supported by metals, have confirmed the importance of adding the elasto-optic contribution to fully interpret the observed spectral features (Sandercock 1978;Loudon and Sandercock 1980). Finally, theoretical studies have been carried out to predict the intensity of surface Brillouin scattering in dielectric and metallic liquids (Dil and Brody 1976;Albuquerque 1983) and the results have been utilized to interpret existing experimental results on alcohols, mercury and gallium (Dil and Brody 1976;Visser et al 1984).…”
Section: Measurements Of Surface Brillouin Scattering On Opaque Matermentioning
confidence: 78%
“…Surface Brillouin scattering is in general not observable in transparent materials, where bulk effects dominate the scattered intensity. Brillouin scattering is a viable method to investigate acoustic wave velocities in opaque solids including metals (e.g., Mendik et al 1992;Graczykowski et al 2011) and metallic liquids (Visser et al 1984) and of metals at high pressures (Crowhurst et al 1999) and it represents a potential method to study the elastic properties of candidate planetary core materials at extreme conditions.…”
Section: Measurements Of Surface Brillouin Scattering On Opaque Matermentioning
confidence: 99%
See 1 more Smart Citation